Evaluasi Kinerja Sistem SIERA pada Badan Pengelolaan Aset Daerah Pemerintah Provinsi DKI Jakarta dengan menggunakan Framework COBIT 5 - Ayu Nindita, Nabilah; Setiawan, Johan; Faza, Ahmad (Journal of Multidisciplinary Issues, 2021)
Objective –To measuring and knowing the level of capability, the value of gaps, and recommendations forimprovement for SIERA information system performance using the framework COBIT 5 based on the processAPO08 Manage Relationship and BAI07 Manage Change Acceptance and Transitioning.Methodology –This research uses a qualitative method and a quantitative method called the mix method. Thequalitative method is used to analyze the level of capability expected from the application of the SIERA informationsystem based on the results of interview answers. In contrast, the quantitative method is used to analyze the level ofcapability that has been achieved so far based on the results of a questionnaire that has been filled out by fourrespondents determined by a convenient sampling technique.Findings – The research found the results that the APO08 domain stopped at level 2, and the domain BAI07 stoppedat desired level 1, so corrective actions need to be taken to reach the level expected level 4.Novelty – By measuring the performance evaluation of the SIERA system, the Regional Asset Management Agencyof DKI Jakarta Province can determine the level of capability that has been achieved and the value of the gap withthe expected level of capability, and assisting the Regional Asset Management Agency of the DKI Jakarta ProvincialGovernment to take corrective actions based on recommendations from the findings in SIERA.Keywords: APO08 Manage Relationship, BAI07 Manage Change Acceptance and Transitioning, COBIT 5, DKIJakarta Regional Asset Management Agency